Strategies to Improve Pore-Size Distribution Characterization of Activated Carbons Using CO and N Isotherms: Volume Regularization and Etched Slit Models - P. F. G. Silvino; D. V. Gonçalves; R. V. Gonçalves; S. M. P. de Lucena; D. C. S. Azevedo (Adsorption Science & Technology)
The pore-size distribution (PSD) of an activated carbon (AC) sample, which is obtained by molecular simulation using a specific probe gas, does not always reproduce the adsorptive behaviour of that sample with other gases. Moreover, different gases generate distinct distributions for the same AC. These facts go against the concept of PSD, which must be unique for a given sample, irrespective of the probe gas used. We analyzed adsorption isotherms of WV-1050 AC sample with nitrogen at 77 K, carbon dioxide at 298 K and methane at 303 K, yielding their respective PSDs, based on local isotherms database (kernels) generated through grand canonical Monte Carlo simulation. The PSD obtained for nitrogen and carbon dioxide was used (individually) to reproduce the three experimental isotherms and significant deviations were observed. By applying a volume normalization methodology, the isotherm fitting was significantly enhanced. Furthermore, a more realistic model of AC pores considering etched slit walls was tested to improve PSD similarity. The new model presented tends to unify the PSDs obtained from different probe gases evaluated.